Adult hookworms (Necator spp.) collected from researchers working with wild western lowland gorillas. Issue 1 (December 2016) - Kalousová, Barbora; Hasegawa, Hideo; Petrželková, Klára; Sakamaki, Tetsuya; Kooriyma, Takanori; Modrý, David
Abstract Background In general, studies on the diversity of strongylid nematodes in endangered host species are complicated as material obtained by non-invasive sampling methods has limited value for generic and species identification. While egg morphology barely allows assignment to family, the morphology of cultivated infective third stage larvae provides a better resolution at the generic level but cannot be used for exact species identification. Morphology-based taxonomic approaches greatly depend on the examination of adult worms that are usually not available. Methods Hookworm parasites in two European researchers, who participated in gorilla research in the Central African Republic, were expelled after anthelmintic treatment to the faeces, collected and morphologically examined. A male worm discharged naturally from a wild bonobo (Pan paniscus ) in Congo was also examined for comparison. Results Two species ofNecator were identified in researchers' faecal material:Necator americanus (Stiles, 1902) andN. gorillae Noda & Yamada, 1964; the latter species differed in having a smaller body, smaller buccal cavity and shorter spicules with spade-shaped membranes situated distally. Males ofN. gorillae also possessed unusual cuticular thickenings on the dorsal side of the prebursal region of the body. These characters, shared with the male worm from the bonobo, correspond well to the description ofN. gorillae described from gorillas in Congo. Conclusions Based on the morphology of the hookworms recovered in this study and previous molecular analyses of larvae developed from both humans and western lowland gorillas (Gorilla gorilla gorilla ) from this locality, we conclude that the researchers became infected with gorilla hookworms during their stay in the field. This is the first report of infection with aNecator species other thanN. americanus in humans.